Population genomic analyses from low‐coverage RAD‐Seq data: a case study on the non‐model cucurbit bottle gourd. (10th December 2013) - Xu, Pei; Xu, Shizhong; Wu, Xiaohua; Tao, Ye; Wang, Baogen; Wang, Sha; Qin, Dehui; Lu, Zhongfu; Li, Guojing
Summary Restriction site‐associated DNA sequencing (RAD‐Seq), a next‐generation sequencing‐based genome 'complexity reduction' protocol, has been useful in population genomics in species with a reference genome. However, the application of this protocol to natural populations of genomically underinvestigated species, particularly under low‐to‐medium sequencing depth, has not been well justified. In this study, a Bayesian method was developed for calling genotypes from an F2 population of bottle gourd [Lagenaria siceraria (Mol.) Standl.] to construct a high‐density genetic map. Low‐depth genome shotgun sequencing allowed the assembly of scaffolds/contigs comprising approximately 50% of the estimated genome, of which 922 were anchored for identifying syntenic regions between species. RAD‐Seq genotyping of a natural population comprising 80 accessions identified 3226 single nuclear polymorphisms (SNPs), based on which two sub‐gene pools were suggested for association with fruit shape. The two sub‐gene pools were moderately differentiated, as reflected by the Hudson's FST value of 0.14, and they represent regions on LG7 with strikingly elevated FST values. Seven‐fold reduction in heterozygosity and two times increase in LD (r2) were observed in the same region for the round‐fruited sub‐gene pool. Outlier test suggested the locus LX3405 on LG7 to be a candidate site under selection. Comparative genomic analysis revealed that the cucumber genome region syntenic to the high FST island on LG7 harbors an ortholog of the tomato fruit shape gene OVATE. Our results point to a bright future of applying RAD‐Seq to population genomic studies for non‐model species even under low‐to‐medium sequencing efforts. The genomic resources provide valuable information for cucurbit genome research.